The Effectiveness and effect of Project-Based Blended Learning on Student Achievement in Online Learning at Surakarta, Indonesia - Salma, Winda Annisa; Basori, Basori; Hatta, Puspanda (Universitas Sebelas Maret, 2021)
Educational technology has a role in the education era 4.0, one of which is utilizing technology-based learning in learning activities in the form of learning applications based on project tasks, namely the Project-Based Blended Learning method. This article aims to get the influence of Project-Based Blended Learning to use on the achievement of students. This study was quantitative research using a pretest-posttest control design. The sample of the study were 72 students. The data were collected by random cluster sampling divided into groups or classes. The hypothesis tests were the independent sample t-test and the gain normalization test based on significant grade 0,05. The result showed significant differences and improvement in student achievement when using the Project-Based Blended Learning from conventional methods in pandemic Covid-19. The result was proven by the hypothesis tests using the T-test that the post-test was 0,000 (0,000<0,05), so the differences in student outcomes between experimental class from control class were found. The gain normalization showed that the experimental class got 0,49 and the control class got 0,16. It can be concluded that there is an improvement in student achievement in the experimental and control classes. Therefore the use of Project-Based Blended Learning contributes more influence to the achievement of students